PENGELOLAAN KINERJA KARYAWAN MELALUI KECERDASAN EMOSIONAL DAN STRES KERJA - Arjuna Rizaldi (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
This study aims to determine and analyze the presence or absence of the influence of employee performance management through emotional intelligence and work stress both partially and simultaneously, considering the performance (performance) is a key factor for each individual and company in achieving productivity in HR employees at PT . PLN (Persero) Distribution of West Java. This research uses descriptive verification method. Primary data in this study were obtained from the results of statements (questionnaires) distributed directly to 32 respondents in the HR Division at PT. PLN (Persero) Distribution of West Java, while secondary data were obtained from data from PT. PLN (Persero) Distribution of West Java. The analytical method used is multiple linear regression analysis using the SPSS v.23 for Windows software application and testing the hypothesis test of the t test and the statistical test of the f test. The results show that the management of employee performance is significantly influenced by emotional intelligence and work stress partially with the direction of a positive relationship of 0.737; Managing employee performance is significantly affected by emotional intelligence and work stress simultaneously showing positive correlations, and in the category of very strong relationships, meaning that the better the emotional intelligence and work stress, the better the employee's performance.